Can you have a migraine aura without knowing it?. Issue 3 (June 2021) - Hadjikhani, Nouchine; Vincent, Maurice
Abstract : Purpose of review: This review covers several aspects our understanding of episodic manifestations and unusual symptoms that may be associated with migraine aura. Recent findings: The episodic manifestation of migraine aura is typically visual in nature, although five other types are currently recognized: sensory, speech and/or language, motor, brainstem, and retinal. Other transitory perceptions or experiences such as emotional, olfactory, or auditory have been reported as possible migraine auras. As underlined by the much higher reported prevalence of aura manifestation in individuals with professional knowledge of its possible manifestations, it appears that a number of migraine auras may remain unnoticed, unreported, or misdiagnosed. Summary: Aura manifestations may be more common, complex, symptom-rich and variable than previously thought. Clinicians should proactively ask questions beyond those addressing visual symptoms when examining individuals with a potential diagnosis of migraine with aura.